Pengaruh Personality Traits, Dan Individual Competencies, Terhadap Knowledge Sharing Dan Employee Performance - Nurjannah Putri Ilyazah; M. Sulhan (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
The purpose of this study is to know the influence of personality traits and individual competencies on knowledge sharing and employee performance. This research was Dinas Pekerjaan Umum dan Penataan Ruang Kota Pasuruan. The data collection technique used is a questionnaire that’s been released online through Google Forms. Selection of research samples using sampling jenuh was 76 respondents. For statistical and data processing, Partial Least Square (WarpPLS 7.0). This result showed: (1) Personality traits (X1) positive and significant effects knowledge sharing (Y1). (2) Individual competencies (X2) positive and significant effects knowledge sharing (Y1). (3) Personality traits (X1) do not affect employee performance (Y2). (4) Individual competencies (X2) positive and significant effects employee performance (Y2). (5) Knowledge sharing (Y1) positive and significant effects employee performance (Y2).